Polymyositis with plasma cell infiltrate in essential mixed cryoglobulinaemia. Issue 3 (March 1993) - Voll, C; Ang, L C; Sibley, J; Card, R; Lefevre, K
Abstract : A patient with essential cryoglobulinaemia who presented with polymyositis is described. Muscle biopsy showed intense plasma cell infiltration of muscle. Plasmapheresis produced a rapid resolution of the cutaneous manifestations of the disease, but little improvement in muscle strength. Oral steroids resulted in moderate improvement in muscle strength. There have been no previously reported cases of polymyositis in association with essential cryoglobulinaemia.